Metacognitive Strategy for Enhancing the Grade XI Students’ Reading Comprehension - Sukmawati, Fitri Sari (English Education: Jurnal Tadris Bahasa Inggris, 2019)
This is classroom action research (CAR) aiming to enhance the students' reading comprehension through metacognitive strategy for Grade XI students of Social Program  (IPS) 2 at senior high school SMA Muhammadiyah 1 Yogyakarta in the 2016/2017 academic year. Involving 37 students, this study was carried out through two stages both of which consisted of seven meetings in total. The CAR stages included determining the problem, planning, action and observation, and reflection. The data were collected by two main techniques. The qualitative data were obtained from the field notes, interview transcripts, and portfolios, and were analyzed through data reduction, data display, and conclusion drawing. Meanwhile, the quantitative data were the reading scores analyzed by the Microsoft Excel program. The results of this study reveal that metacognitive strategy is somewhat successful in improving the students’ participation, learning independence, and reading comprehension. In-group learning was believed to render higher improvement by the metacognitive strategy, from 72.19 in Cycle 1 to 76.43 in Cycle 2 or a gain score of 4.24, and it supports the teacher in variatively managing the classroom activities, learning materials, and reading instructions.